Use of Google Analytics to Explore Dissemination Activities for an Online CKD Clinical Pathway: A Retrospective Study. (May 2022) - Chong, Christy; Smekal, Michelle; Hemmelgarn, Brenda; Elliott, Meghan; Allu, Selina; Wick, James; McBrien, Kerry; Jackson, Wes; Bello, Aminu; Jindal, Kailash; Scott-Douglas, Nairne; Manns, Braden; et al.
Background: Data on dissemination strategies that generate awareness of clinical pathways for kidney care are limited. Objective: This study reports the application of Google Analytics to describe the reach and use of the Chronic Kidney Disease Pathway (CKD-P) using a multi-faceted dissemination strategy. Design: The design of this study is a retrospective descriptive study. Setting: This study was conducted in Alberta, Canada. Patients: Individuals who accessed the CKD-P Web site between November 5, 2014, and May 31, 2019. Measurements: Dissemination activities included print, electronic, in-person meetings, and a laboratory prompt. We used Google Analytics over a 5-year period to evaluate the following CKD-P Web site user metrics: number of sessions, pageviews, visit duration, user path, and bounce rate (when an individual visits a single page of the Web site and leaves the Web site without interacting with additional pages). Methods: We plotted dissemination activities alongside Web site metrics using control charts and described the data using means and percentages. We performed chi-square test for trends to evaluate year-over-year usage. Results: There were 83 294 users, 90 805 sessions, and 231 684 pageviews. The overall bounce rate was 45.7%. Each user had an average of 1.5 sessions and a session duration of 2 minutes and 8 seconds. There was a significant positive trend for total annual users ( P = .008), new users ( P = .009), number of sessions ( P = .006), and pageviews per day ( P = .016). Limitations: We were unable to confirm if users were primary care providers and if word-of-mouth dissemination among providers/researchers drove people to use the CKD-P. Conclusions: Google Analytics was a useful and accessible tool for evaluating CKD-P reach and use trends. It was challenging to identify how individual dissemination activities contributed to CKD-P reach; however, repeated dissemination appeared to play a role in increasing CKD-P use. Trial registration: Not applicable—observational study design.